Influence of principals' readiness for change on school effectiveness - Padzil, Iskandar; Abdul Kadir, Suhaida; Mohd Ayub, Ahmad Fauzi; Arshad, Mohd Mursyid (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
The purpose of this study is to investigate the influence of principals’ readiness for change on school effectiveness in secondary schools. The data were collected from 246 principals in low performance school in East Malaysia by cross sectional study method. Readiness for Organizational Changes instrument was used to measure the principals’ level of readiness for change while School Effectiveness Questionnaire was used to measure the principals’ perception towards school effectiveness. The education reforms and recent changes in Malaysia education need all the school leaders to move towards high performing school status. In order to ensure that a school achieves this goal, School Improvement Partners Plus (SIPartners+) was placed in every districts in Malaysia to help the principals in school management and improving their leadership skills. Hence, this processes require high commitment and readiness for change from the principal to adapt the transformation which lead to the school effectiveness. Four main constructs of readiness for changes -appropriateness of changes, management support, change efficacy and personal valence were used as predictors to school effectiveness. The analysis results showed that there is a significant influence between principals’ readiness for change with the school effectiveness. Regression analysis result showed that appropriateness of change and management support were main predictors of school effectiveness. This research findings revealed some meaningful implications to the body of knowledge generally to the Ministry of Education or specifically to the principals and school development.